2009
DOI: 10.5392/jkca.2009.9.2.270
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on Mobile Web Browsing Service Adoption

Abstract: Mobile web browsing services that bring the full PC browsing experience to customer's mobile handset have been emerged. This study is to investigate the intention to use mobile web browsing based on Technology Acceptance Model(TAM) which has been widely used to explain and predict the IT acceptance and incorporated with self-efficacy which was identified as an important determinant of user's new technology adoption in recent literature on technology acceptance. Specifically, from a theoretical perspective, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Hardware quality has also been studied in mobile Internet contexts. Ryoo et al [2009] examined and found a causal relationship between ease of use of mobile Web browsing devices and positive attitude for the service. One of the most outstanding advantages of mobile technology is the ability to enable anytime, anywhere access [Sarker and Wells, 2003], and the capability of ubiquity can affect behavior intention to use [Kim and Garrison, 2009;Looney et al, 2004].…”
Section: Figure 1 Determinants Of Actual Use Of Mobile Web Browsing mentioning
confidence: 99%
See 2 more Smart Citations
“…Hardware quality has also been studied in mobile Internet contexts. Ryoo et al [2009] examined and found a causal relationship between ease of use of mobile Web browsing devices and positive attitude for the service. One of the most outstanding advantages of mobile technology is the ability to enable anytime, anywhere access [Sarker and Wells, 2003], and the capability of ubiquity can affect behavior intention to use [Kim and Garrison, 2009;Looney et al, 2004].…”
Section: Figure 1 Determinants Of Actual Use Of Mobile Web Browsing mentioning
confidence: 99%
“…Ajzen, 2001;Davis, 1989;Karahanna and Limayem, 2000;Taylor and Todd, 1995]. Most of the recent studies on the acceptance of mobile technologies, including mobile data services and mobile Internet, tested the relationship between attitude and behavioral intention, since, at the time of the studies, mobile technologies were still in their early stage of diffusion [Nysveen et al, 2005;Ryoo et al, 2009]. In this study, however, we further verify the theorized relationship between attitudes and actual use in the mobile Web browsing services context by directly measuring self-reported actual use rather than behavioral intention to use mobile services.…”
Section: Antecedents Of Actual Usementioning
confidence: 99%
See 1 more Smart Citation